Vegetation-environment relationships based on a life-forms c1assification in a semiarid region of Tropical Mexico - Zavala-Hurtado, J A; Valverde, P L; Díaz-Solís, A; Vite, F; Portilla, E (Revista de Biología Tropical, 1996)
Taking the view that morphological characteristics represent behavioral strategies of plants to cope with environmental pressures, we defined 18 life-forrns, using multivariate classification techniques in a tropical semiarid ecosystem in Central Mexico. A multiple discriminant analysis confirrned the existence of these groups. A nul! model of random rnembership of species to life-forrns was significantly different from our classification. Vegetation-envíronment relationships were exanúned wíth Detrended Canonical Correspondence Analysis (DCCA). Ordínation axes were ínterpreted mainly by altitude and soíl moisture. Response curves of life-forrns along these gradients were explored fitting generalized linear models (OLIM’s). We believe that the life-forrns approach for the study of vegetation-envíronment relationships ís a valid alternative to the tradítional specíes approach usually used in phytosociological research because: í) lífe-forrns number was found to be an excellent specíes diversity predictor, ii) this approach enables considerable reduction in the bulk of data without losing ecological inforrnation, and iíi) life-forrns represent ecological strategies per se and, they constitute an index of the number of different ways the desert’s resources are utilízed